Chlamydia trachomatis exploits sphingolipid metabolic pathways during infection of phagocytes - Adriana Moldovan; Fabienne Wagner; Fabian Schumacher; Dominik Wigger; David Komla Kessie; Marcel Rühling; Kathrin Stelzner; Regina Tschertok; Louise Kersting; Julian Fink; Jürgen Seibel; Burkhard Kleuser; et al. (mBio)
ABSTRACT Chlamydiae are obligate intracellular pathogens that utilize host cell metabolites for catabolic and anabolic processes. The bacteria replicate in epithelial cells from which they take up sphingolipids (SL) and incorporate them into the chlamydial membrane and the vacuole (termed inclusion). SL uptake is essential for Chlamydia trachomatis (Ctr) in epithelial cells; however, they can also infect phagocytes, but the consequences for the SL metabolism have not yet been investigated in these cells. We performed a quantitative sphingolipidome analysis of infected primary neutrophils, macrophages, and immortalized fallopian tube epithelial cells. Sphingosine (Sph) levels are elevated in primary M2-like macrophages and human neutrophils infected with C. trachomatis. Human neutrophils respond to the pathogen by markedly upregulating sphingosine kinase 1 (SPHK1). We show in M2-like macrophages, by RNAseq, that two counteracting pathways involving upregulation of SPHK1, but also sphingosine-1-phosphate phosphatases 1 and 2 (SGPP1 and SGPP2) and sphingosine-1-phosphate lyase (SGPL1), maintain a steady pool of S1P. Using click chemistry, we show that exogenously added sphingomyelin (SM) and ceramide (Cer) are efficiently taken up into the chlamydial inclusion and are integrated into bacterial membranes in infected M2-like macrophages. Exogenous Sph reduces chlamydial infectivity, is transported into the inclusion lumen, and integrates into chlamydial membranes, suggesting that this particular SL species could represent a host defense mechanism. Taken together, our data indicate an important role for Sph/Sph kinase vs S1P/S1P phosphatase balance in infected phagocytes and a previously unrecognized role for sphingosine in the immune defense against chlamydial infection.IMPORTANCEChlamydia trachomatis (Ctr) is the leading cause of sexually transmitted diseases worldwide. Left untreated, it can cause severe complications such as blindness, pelvic inflammatory disease, or infertility. To date, no vaccines are available, and antibiotic treatment represents the only therapeutic approach to cure the infection. Limited access to antibiotics and displaced antibiotic intake increase the risk of developing recurring infections. Immune cells which fail to clear the infection and serve as a niche for chlamydial survival and replication, favor this outcome. Our research aims to elucidate the influence of sphingolipids (SL) during chlamydial infection, especially of phagocytic cells. Identifying relevant targets offers new strategies to develop alternative treatment methods.